Evolutionary game analysis on technological innovation strategies of marine ranching enterprises considering government’s incentive policies and consumer preferences - Liu, Haodong; Wu, Qian (Frontiers in Marine Science, 2024)
As a new mode of marine industry, marine ranching is gradually becoming an important means to promote the high-quality development of marine economy. Meanwhile, the technological innovation of marine ranching enterprises (MREs) can enhance the economic and ecological functions of marine ranching. This paper builds an evolutionary game model including MREs, government and consumers to analyze strategic choices. The results show that: (1) The government’s incentive policies play a key role in the initial period of MREs, while the government can gradually eliminate the policies in the mature period of MREs. (2) Government’s incentive policies consist of subsidy and tax policies. The subsidy amount should be moderate in order to avoid financial burdens, and the tax policy should be adaptation to different types of MREs. (3) Consumers’ preference significantly affects the strategy of MREs innovation. Government subsidies for consumers with different preferences can guide market demand and provide market signals for MREs. This study provides an important reference for MREs to formulate technological innovation strategy and the government to formulate relevant policies